Self-Reported Sleep Duration, Sleep Quality, and Breast Cancer Risk in a Population-Based Case-Control Study - Girschik, J.; Heyworth, J.; Fritschi, Lin (Oxford University Press, 2013)
Breast cancer is one of the most commonly diagnosed invasive cancers. Established risk factors account for only a small proportion of cases. Previous studies have found reductions in sleep duration and quality in the general population over time. There is evidence to suggest a link between poor sleep and an increased risk of breast cancer. In this study, we investigated the relationship between breast cancer and sleep duration and quality in Western Australian women. Data were obtained from a population-based case-control study conducted from 2009 to 2011. Participants completed a self-administered questionnaire that included questions on sleep. Odds ratios and 95% confidence intervals were calculated using unconditional logistic regression. Sensitivity analysis for potential selection and misclassification bias was also conducted. We found no association between self-reported sleep duration on workdays and risk of breast cancer (for <6 hours, odds ratio (OR) = 1.05 (95% CI: 0.82, 1.33); for 6–7 hours, OR = 0.96 (95% CI: 0.80, 1.16); and for >8 hours, OR = 1.10 (95% CI: 0.87, 1.39),compared with the reference category of 7–8 hours’ sleep). In addition, we found no association between sleep duration on nonworkdays, subjective sleep quality, or combined duration and quality and risk of breast cancer. This study does not provide evidence to support an association between self-reported sleep duration or quality and the risk of breast cancer.